Effects of tempol on renal angiotensinogen production in Dahl salt-sensitive rats - Kobori, Hiroyuki (2004)
We have recently reported that Dahl salt-sensitive rats (DS) on high salt diet (HS) have an inappropriate augmentation of intrarenal angiotensinogen. Recent studies also reported that the augmented superoxide anion formation plays important roles in this animal model of hypertension. This study was performed to address the hypothesis that an inappropriate augmentation of intrarenal angiotensinogen by HS is caused by the augmented reactive oxygen species. Male DS (200–220 g) were maintained on low salt diet LS (N = 7) or HS (N = 27) for 4 weeks. The HS group was subdivided into three subgroups to receive null (N = 12), superoxide dismutase mimetic, tempol (3 mmol/l, N = 8), or vasodilator, hydralazine (0.5 mmol/l, N = 7) in drinking water during the period. Systolic BP was significantly increased in the DS + HS group compared to the DS + LS group (184 ± 7 mmHg vs. 107 ± 5 at 4-week). Tempol or hydralazine treatment equivalently attenuated the hypertension (128 ± 3 and 127 ± 5 at 4-week, respectively). Urinary excretion of thiobarbituric acid reactive substances at 4-week was significantly increased in the DS + HS group compared to the DS + LS group (0.66 ± 0.05 µmol/day vs. 0.14 ± 0.01). Tempol treatment prevented this effect (0.24 ± 0.04) but hydralazine treatment only partially prevented the effect (0.40 ± 0.03). Kidney angiotensinogen levels, measured by Western blot analysis, were significantly increased in the DS + HS group compared to the DS + LS group (32 ± 5 densitometric units vs. 21 ± 1). Tempol (14 ± 3) but not hydralazine (32 ± 5) treatment prevented the intrarenal angiotensinogen augmentation. The evidence suggests that the enhanced intrarenal angiotensinogen in DS challenged with HS is associated with the augmented reactive oxygen species.